AUGMENTED REALITY FOR MEDICAL TRAINING: ADVANCING MEDICAL EDUCATION AND SURGICAL TRAINING WITH AR - Preetish Kakkar; Arjun Jaggi , (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2021)
Augmented reality (AR) is revolutionizing medical education and surgical training by simulating real-world environments for skill enhancement in a safe and controlled setting. By overlaying digital information, such as 3D models and real-time patient data, AR creates immersive learning experiences, particularly in anatomy instruction. In surgical training, AR improves accuracy by providing real-time guidance, enhancing precision during complex procedures, and allowing residents to practice in a simulated operating environment. As medical training evolves, AR plays a crucial role in bridging the gap between theoretical knowledge and practical application.